VISIBLE LIGHT COMMUNICATION (VLC) SYSTEM FOR AUDIO TRANSMISSION - Muhamad Irham Ma'ruf; Sholeh Hadi Pramono; Maisara Binti Othman (Jurnal Mahasiswa TEUB, 2015)
Limited radio frequency spectrum (or bandwidth) is one of the major issues in wireless communication. Visible light communication (VLC) should be considered as the medium for wireless transmission because it has few advantages over other standard wireless transmissions. The advantages of VLC are low power consumption. The visible light spectrum have 10,000 times larger than the entire radio frequency spectrum which ranges from 428 THz to 750 THz. In this project the performance of visible light communication have been tested on the variation of distance between transmitter and receiver. Besides that the influence of the additional amplifier at the transmitter and receiver on the VLC system are also been characterized. Based on the results and analysis the implementation of the amplifier circuit at the transmitter and receiver helps to improve the signal quality of the audio signal in the VLC system. However the amplifier also increased the noise in this system. Moreover, the distance between transmitter and receiver can give influence to the system performance. The longer the distance means that the signal strength and voltage which has been received by the receiver decreased and cause the data loss in the system. As a conclusion this audio transmission in the VLC system are working properly and have been successfully demonstrated. However the maximum of distance between transmitter and receiver is limited to 20 cm.Keywords – Wireless Communication, Visible Light Communication, Audio Transmission